Optimization of Professional Equipment in Improving Economic Welfare in Zakat Financial Institution - Saputri, Yuli Dahlia; Noviarita, Heni (Dirham: Journal of Sharia Finance and Economics, 2026)
Purpose: This study aims to analyze zakat management optimization, focusing on professional zakat in zakat financial institutions, to improve economic welfare in Indonesia. Methods: A qualitative descriptive research approach was used, combining field research and literature review. Interviews were conducted with key stakeholders in zakat management, and secondary data from zakat institutions were analyzed. Results: The study found that optimizing professional zakat involves aspects such as the potential of zakat payers (muzakki), institutional professionalism, zakat publication efforts, commitment from zakat payers, and effective distribution methods. However, challenges remain, including insufficient stakeholder support and low awareness of professional zakat among muzakki. Conclusions: The study concludes that effective zakat management, especially professional zakat management, can significantly improve economic welfare. This requires the efficient collection, distribution, and utilization of zakat funds by professional institutions such as BAZNAS, supported by better stakeholder engagement and public education. Limitations: This research is limited to zakat financial institutions (BAZNAS) and does not explore other types of zakat or zakat institutions. Additionally, data on zakat management practices from different regions were not gathered comprehensively. Contributions: This research provides valuable insights into the role of professional zakat in improving economic welfare and offers recommendations for better zakat management in Indonesia. This study contributes to the understanding of how zakat can be optimized for societal benefit, particularly in Indonesia.